Scoping the contextual issues that influence shrinkage measurement. - Chapman, Paul; Templar, Simon (Emerald Group Publishing Limited, 2006)
Measures and measurement systems must reflect the context to which they are applied (Neely, 1999), requiring that the contextual issues relating to retail shrinkage must be identified as a necessary precursor when measuring shrinkage. Without considering these issues any decision on which method of shrinkage measurement to employ will be uninformed, arbitrary and at best intuitive.